New maximum size record for the Goonch Bagarius yarrelli (Sykes, 1839) (Siluriformes: Sisoridae) from the Ganges River - Md. Yeamin Hossain (Universiti Kebangsaan Malaysia, 2010)
On 3 January 2008, one specimen of GoonchBagarius yarrelli (Sykes 1839) (Siluriformes: Sisoridae) was caught by a conventional beach seine in the lower part of the Ganges River, NW Bangladesh. The specimen constitutes a new record of maximum length and weight for the Ganges River and the South Asia.